Catalonia - Dowling, Andrew, 1965 July 18- author.
1 online resource (177 pages).
Keywords: "Catalonia: A New History revises many traditional and romantic conceptions in the historiography of a small nation. This book engages with the scholarship of the past decade and separates nationalist myth-history from real historical processes. It is thus able to provide the reader with an analytical account, situating each historical period within its temporal context. Catalonia emerges as a territory where complex social forces interact, where revolts and rebellions are frequent. This is a contested terrain where political ideologies have sought to impose their interpretation of Catalan reality. This book situates Catalonia within the wider currents of European and Spanish history, from pre-history to the contemporary independence movement, and makes an important contribution to our understanding of nation-making"--